POLICE OFFICER’S EXPECATTIONS AS A FIRST RESPONDER IN ROAD TRAFFIC ACCIDENTS: A QUALITATIVE STUDY - Ikhda Ulya; Retty Ratnawati; Kumboyono Kumboyono (Journal of Nursing Science Update (JNSU), 2019)
Police officers are first responder with special lay category. Police have an additional duty to provide first aid to victims of accidents because medical personnel are still limited to provide help. Certainly the police have their own experience that needs to be explored to find out what expectations are for their daily activities in helping victims of current traffic accidents. This study used a qualitative design of hermeneutic phenomenology to explore and interpret police officers' expectations as first responder in traffic accident victims. The number of participants as many as 5 people who served at the Post Purwodadi Lands Area Pasuruan Police. Instruments in this study that researchers as a core instrument and other supporting tools that is in the form of a netbook equipped with a camtasia studio voice recorder program, ballpoint pen, and paper for field notes. Data collected through indepth interview processed into tranksrip and then analyzed by using method Dikelmann et al (1989). The results of the research are two cross-sectoral cooperation and the need for an award. The theme of cross-sector cooperation is built on two sub themes, namely cooperation with hospitals and cooperation with the community. The theme of need for an award is built by a sub theme that needs rewards. The conclusion of this research is that police officers have big expectation to the related parties to give the best first aid for the safety of traffic accident victims. Thus, it is hoped that the cooperation will be strengthened to support police officers in helping victims of traffic accidents to reduce the mortality and morbidity of traffic accident victims.